The Effectiveness of technology-based Islamic education learning in the digital era at SMAN 1 Bojonegoro - Anggraini, Febiana; Aprillia, Mita; Syahputra, Reva Khusnun; Silmi, Thoriq Aji (Asatiza: Jurnal Pendidikan, 2024)
Technology has become an integral part of daily life, including the field of education, where it provides broad access to information and resources. This study aims to examine the implementation of technology-based Islamic Religious Education (PAI), which is equivalent to Islamic Education, at SMAN 1 Bojonegoro. Utilizing a qualitative method with descriptive analysis, data were collected through observation, interviews, and documentation to ensure the validity of the information. The research subjects included PAI teachers and selected students from SMAN 1 Bojonegoro. The findings show that the implementation of technology-based PAI learning, using platforms such as Quizizz, Microsoft PowerPoint, and Google Classroom, has proven to be effective. Students demonstrated more active and engaging interaction, which in turn enhanced their understanding of PAI materials. These findings indicate that integrating technology into PAI learning can provide significant benefits to the teaching and learning process.